Malic enzyme tracers reveal hypoxia-induced switch in adipocyte NADPH pathway usage - Liu, Ling (Nat Chem Biol, 2016)
The critical cellular hydride donor NADPH is produced through various means, including the oxidative pentose phosphate pathway (oxPPP), folate metabolism and malic enzyme. In growing cells, it is efficient to produce NADPH via the oxPPP and folate metabolism, which also make nucleotide precursors. In nonproliferating adipocytes, a metabolic cycle involving malic enzyme holds the potential to make both NADPH and two-carbon units for fat synthesis. Recently developed deuterium ((2)H) tracer methods have enabled direct measurement of NADPH production by the oxPPP and folate metabolism. Here we enable tracking of NADPH production by malic enzyme with [2,2,3,3-(2)H]dimethyl-succinate and [4-(2)H]glucose. Using these tracers, we show that most NADPH in differentiating 3T3-L1 mouse adipocytes is made by malic enzyme. The associated metabolic cycle is disrupted by hypoxia, which switches the main adipocyte NADPH source to the oxPPP. Thus, (2)H-labeled tracers enable dissection of NADPH production routes across cell types and environmental conditions.